2015
DOI: 10.22460/p2m.v2i1p77-90.167
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of English Summative Tests at Junior High School in West Bandung

Abstract: This study is purposed to measure the validity and reliability of English summative test items for the third grade of Junior High School in West Bandung. This research is categorized as quantitativedescriptive analysis because it is intended to describe the difficulty level, discriminating power, distracters effectiveness, validity and reliability of the English Summative Test. The finding of this study are that there are 16 items (53,33%) regarded as easy test items in difficulty level that range from 70-1.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 9 publications
2
12
2
1
Order By: Relevance
“…In contrast to those six previous studies, Haryudin (2015) found that the difficult items are more than other categories item. In their analysis of item difficulty, these previous researches point out that those test packages have more poor-constructed items than well-constructed items.…”
Section: Item Difficultycontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to those six previous studies, Haryudin (2015) found that the difficult items are more than other categories item. In their analysis of item difficulty, these previous researches point out that those test packages have more poor-constructed items than well-constructed items.…”
Section: Item Difficultycontrasting
confidence: 99%
“…Numerous studies have attempted to explain the item difficulty in relation to analyze the tests quality (for example Amelia, 2010;Maghfiroh, 2010;Ani, 2011;Risydah, 2014;Haryudin, 2015;Manfenrius et al, 2015;Maghfiroh, 2019;Pradanti et al, 2018). Some analysts, (e.g.…”
Section: Item Difficultymentioning
confidence: 99%
See 2 more Smart Citations
“…The result was in harmony with the result of Primadani (2013) and Haryudin (2015). The high reliability of the test was due to the number of items which were crucial for test reliability.…”
Section: Reliabilitysupporting
confidence: 81%